(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Free radicals are implicated in many diseases, including cancer, diabetes mellitus, arthritis, ageing. etc., In the treatment of these diseases, antioxidant therapy has gained very importance. Various extracts of Carissa carandas L were studied for its in vitro antioxidant activity used different models viz. ABTS radical scavenging, DPPH radical scavenging, H2O2, Hydroxyl radical, lipid peroxidation and Super oxide. The results were analyzed statistically by the regression methods. The scavenging effect of plant extracts and standardized (L. ascorbic acid) on the various scavenging methods in the following order L-ascorbic acid Ethanol Ethyl acetate Chloroform Pet ether. Its antioxidant activity was estimated by IC50 values and the values are 124.62 TO276.42μg/ml (ABTS radical scavenging), 205.24TO 354.52 μg/ml (DPPH radical scavenging), 168.12 TO 262.48 μg/ml (Hydrogen peroxide), 204.06 to 292.44 μg/ml (Hydroxyl radical), 154.02 to 310.22 μg/ml (Lipid peroxidation), 161.84 to 360.44μg/ml (Super oxide). In all the testing, a significant correlation existed between concentrations of the extract and percentage inhibition of free radicals, metal chelation or inhibition of the liquid peroxidation. The antioxidant property may be related to the polyphenols and flavonoids present in the extract. The results clearly indicate that Carissa carandas L is effective against free radical mediated disease.